Etika Mengkritik Pemerintah Menurut Buya Hamka dan Wahbah Az-Zuhaili atas QS. Thaha Ayat 43-48 - Cintana, Ayu; Ahmad Zainal Abidin; Muhammad Ridho; Nurul Hidayat; Zunita Lut Fiana Pangesti (Jurnal Semiotika Quran, 2023)
This article discusses the ethics of criticizing the government in Thaha's letter verses 43-48 from the perspective of Buya Hamka and Sheikh Wahbah az-Zuhaili. This is based on the thoughts of Buya Hamka and Wahbah who provide different examples of the ethics of criticizing the government. This article will compare thoughts on the ethics of government criticism between Buya Hamka and Wahbah az-Zuhaili in their respective interpretations. The method used in this article is comparative descriptive, namely explaining the differences and similarities between the interpretations of the two commentators.  The findings reveal that there are similarities as well as differences between the interpretations of Buya Hamka and Wahbah az-Zuhaili. The similarities found in the two interpretations are the meaning of the characteristics of mastery that goes beyond limits, the meaning of the technique of hitting with soft language, the content of the criticism conveyed by Musa Harun to Pharaoh, as well as the validity of the criticism conveyed by both of them to Pharaoh. The difference in the two interpretations is the style of language used by both of them in explaining the characteristics of those in authority and when hitting them using gentle language, then the meaning contained in fear when hitting people with high power, also presents different supporting data.